AKTIVITAS KONTRASEPSI DAN INTERSEPSI EKSTRAK METANOL DAUN BENALU Dendrophthoe petandra L PADA MENCIT - G N Astika (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2000)
It had been reported that leaf of Dendrophthoe petandra contained a flavonol glycoside of which quercetion was its aglycone. In-vitro study in the activity of quercetin indicated that quercetin inhibited the activity of sperm hyaluronidase. So it meant quercetin inhibited sperm penetration into cumulus. Other study proved that quercetin inhibited the activity of cytochrome P-450 III A 4 enzyme which catalyzed the reversible hydroxylation of estradiol-17Î² into estrone and futher into estriol. The elevation of estradiol serum level disturbed gamete and zygote transport in oviduct causing premature expulsion of zygote into uterus. This research was designed to provide information about the anti-fertility activity of methanolic extract of leaf of Dendrophthoe petandra, focused on its contraceptive and interceptive activity. Virgin female Balc-C mice were used as the test animals. Each study had two group of mice which were treated with 150 mg/30 g and 200 mg/30 g extract respectively. Control group were treated with respective vehicle at 1 ml/30 g. statistical analysis of data (p<0.05) concluded that the extract had contraceptive and interceptive activity. According to the criterion given by Lee andChi (1985), this methanolic extract had a priority for further study.